Internal audit, a tool to improve the quality of financial statements in Algerian economic institutions - case study of limited liability company "SS" - chikhi, selma; Riad, meriem (Journal of Research in Finance and Accounting, 2021)
This study aims to determine the importance of internal auditing in improving the quality of financial statements, since it's a major tool in making various decisions by its users. In fact economic institutions found themselves suffering from proper disclosure problems and that is what prompted them to look for effective ways to ensure credible and quality financial statements. The study concluded that through his auditing mission for fixed assets, the internal auditor of "SARL SS" is able to help improve the quality of financial statements by identifying the strengths and weaknesses that characterize the internal control, and make recommendations to correct the deficiencies resulting from some administrative procedures, as well as accounting errors related to fixed assets.